Integrated Systems: Innovations and Applications - Fathi, Madjid (Springer, 2015)
Integrated systems and technologies are successful multi-disciplinary approaches in which the integration is the most efficient factor with regard to emerging technologies. Enterprises and industrial parties, nowadays, need to be aware of key technologies not only in their respective fields, but also widen perspectives of the other sectors. Most of multi-disciplinary approaches in these integrated systems lead to the substantial inno vation and the creation of novel ideas. Enhanced usability of the whole platform, better parameterization of algorithms, more efficient management of resources and improved performance during the end-to-end processes are just a few advantages of these inte grated platforms. We are pleased to coordinate an annual scientific event in order to distinguish disciplines within the scope of industrial, medical and other diverse sec tors. This annual event is entitled Integrated Systems Design and Technology (ISDT) conference.